SOLUBILITY AND DISSOLUTION RATE ENHANCEMENT OF EZETIMIBE BY SOLID DISPERSION AND PELLETIZATION TECHNIQUES USING SOLUPLUS AS CARRIER - Kunam, Viswanadh; Suryadevara, Vidyadhara; Garikapati, Devala Rao; Mandava, Venkata Basaveswara Rao; Sasidhar, RLC (International Journal of Applied Pharmaceutics, 2019)
Objective: In the present investigation, an attempt was made to improve the surface characters and solubility of the drug by solid dispersion and coating it on the nonpareil sugar beads as pellets. Methods: Ezetimibe solid dispersions were prepared by kneading method using soluplus. Crospovidone was added as a disintegrant in pellets. Ezetimibe pellets were prepared by dissolving soluplus and crospovidone in ethanol in different ratios and coated on nonpareil sugar beads as a drug layer by pan coating technique. Various physicochemical parameters like particle size, friability, angle of repose and drug content were evaluated for the prepared solid dispersions and pellet formulations. In vitro dissolution studies were carried out in 1% SLS using USP apparatus II. FTIR and SEM analysis were performed for solid dispersions, pellet formulations and its polymers to determine the interactions and surface characteristics. Results: The physicochemical parameters were within the specified I. P limits. It was observed that the solid dispersion formulation ED5 showed better dissolution rate to the extent of 1.07 folds and 1.95 folds when compared to a marketed formulation and the pure drug, respectively. Similarly, pellet formulation EP5 containing 1:5 ratio of ezetimibe to soluplus showed an improved dissolution rate to the extent of 1.173 folds and 2.136 folds when compared to the marketed formulation and the pure drug, respectively. FTIR analysis revealed that there was no major interaction between the drug and the excipients. Conclusion: From the present study, it was observed that the solubility of ezetimibe was enhanced by soluplus in pellet formulations when compared to solid dispersions.